THE USE OF PROCESSING MICROFINANCE IN THE AGRICULTURAL SECTOR FOR REGULATING TEMPERATURE AND MOISTURE LAND IN A REMOTE MANNER - Bisman Perangin-Angin; Ainun Mardiyah Lubis Mardiyah Lubis (AGRIUM: Jurnal Ilmu Pertanian, 2016)
This study is an engineering and technology to take advantage of micro processors (mikrokotroller) in the field of agriculture to regulate the temperature and soil moisture. This tool uses a microcontroller ATMega 8535 and sensor SHT11 to measure temperature and humidity, RS-232, LCD, and is equipped with a GSM module that will be used as the control system remotely, as well as several actuators as controlling and safeguarding the stability of the blower (fan) and sprayer water. Software on the device using Bascom AVR programming language. This tool is used to measure and control the temperature and soil moisture is lacking distance. The results of sensor readings SHTT-11 will be processed by a microcontroller and instantly displayed on the LCD. If the measurement results of sensor SHT11 exceed specified limits on the microcontroller, the microcontroller will send data via RS232 GSM to GSM modem then sends the data to the Cellular Telephone. From mobile phones sent commands to the microcontroller to turn the actuator. This tool has been tested and the results are in accordance with the expected.Keywords: Humidity, Temperature Microcontroller, Sensor SHT11, GSM